Determination of the levels of some selected metals in ocimum lamiifolium in Wolaita Zone, Southern Ethiopia - Eyob Yishak; Teferi Tademe Dadebo (East African Journal of Biophysical and Computational Sciences)
Medicinal plants have worldwide applications in the treatment of different types of human diseases. Among the medicinal plants of Ethiopia, Ocimum lamiifolium Hochst. Ex Benth (Damakese, in Amharic) is one of the well celebrated and most widely used home remedy for the treatment of a disease locally known as “Mitch” which is characterized by headache, fever, inflammation, joint pain, sweat, loss of appetite, etc. The aim of the present study on this medicinal plant was to determine the levels of heavy and trace metals in the leaves using the flame atomic absorption spectrometer (FAAS), which is nov AA model. The sampling technique used to carry out the analysis was purposive for the community in the selected area use the plant widely to treat different diseases. In addition, for each of three kebeles, selected from Duguna Fango District, three sites were selected to homogenize the samples. The concentrations or levels of heavy and trace metals, Cd, Co, Pb, Cr, Cu and Zn, in the leaves of the selected medicinal plant were  found to be (in mg/L) 0.0489, 0.0579, 0.0936, 0.153, 0.214 and 0.847, respectively. The results revealed that the selected medicinal plant accumulated these metals at different concentration levels in different sites. The results also confirmed that the concentration levels of the metals in the leaves of the selected medicinal plant were not higher than the internationally accepted permissible limits. Thus, the results indicated thatthe medicinal plant under the study is safe for medicinal uses. Furthermore, monitoring such medicinal plants for heavy and trace metals concentrations is of great importance in protecting the community from the adverse effects of the heavy metals.